2018
DOI: 10.1063/1.5054636
|View full text |Cite
|
Sign up to set email alerts
|

Structure modulation induced enhancement of microwave absorption in WS2 nanosheets

Abstract: This work reports the structural phase manipulation and the enhancement of microwave absorption in WS2 nanosheets. Large-scale WS2 nanosheets (1T@2H WS2) containing mixed 2H and 1T phases were synthesized by a simple hydrothermal process. The structural characteristics and concentration (∼60%) of the 1T phase in 1T@2H WS2 nanosheets were identified by X-ray diffraction, Raman spectroscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. With the emergence of the 1T phase, the permittivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…Innovative solutions in modern electronics are mostly based on applications of new types of materials. [1][2][3][4][5][6][7] Graphene, a monolayer thick allotrope of carbon, is a 2D material, which shows mechanical flexibility and very high mobility of charge carriers complemented by unusual optical transparency in the range of visible light. [8][9][10][11][12] It is believed that graphene can serve as a conducting transparent electrode in organic light-emitting diodes (OLEDs) and organic photovoltaics (OPVs) [13][14][15][16][17][18][19][20][21][22] due to its low resistance below 50 Ω □ À1 and optical transmittance of at least 90%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative solutions in modern electronics are mostly based on applications of new types of materials. [1][2][3][4][5][6][7] Graphene, a monolayer thick allotrope of carbon, is a 2D material, which shows mechanical flexibility and very high mobility of charge carriers complemented by unusual optical transparency in the range of visible light. [8][9][10][11][12] It is believed that graphene can serve as a conducting transparent electrode in organic light-emitting diodes (OLEDs) and organic photovoltaics (OPVs) [13][14][15][16][17][18][19][20][21][22] due to its low resistance below 50 Ω □ À1 and optical transmittance of at least 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative solutions in modern electronics are mostly based on applications of new types of materials . Graphene, a monolayer thick allotrope of carbon, is a 2D material, which shows mechanical flexibility and very high mobility of charge carriers complemented by unusual optical transparency in the range of visible light .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11a,e 4c,12 ] Several studies have provided evidences that the 1T phase has a beneficial effect for achieving better EMW attenuation of TMDs compared to its semiconducting counterpart (2H‐MoS 2 ). [ 5,9b,13 ] The recent work reported by Che et al. found that the unique crystalline phase switch between 2H and 1T phase in rose‐like 1T@2H‐MoS 2 /rGO composites was considered to ameliorate the related EMW absorbing performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9b ] Our previous work also verified that the MoS 2 and WS 2 with moderate content of metallic 1T phase endow the advantages of boosting the EMW absorbing performance over that of pure 2H‐MoS 2 . [ 5,13 ] In view of the superior properties of 1T phase of TMDs, one can expect that the phase manipulating toward MoS 2 (i.e., tuning the 2H/1T phase ratio inside) would be an effective strategy to boost the EMW absorbing performance by the synergistic effect of phase interfaces manipulation and large 2D specific surface area. [ 11b,14 ] Nevertheless, three major challenges standing in front of the researchers: i) how to obtain the stable 1T phase regardless of its intrinsic metastable properties; ii) the MoS 2 with 2H and 1T phases should be synthesized in a manner that results in high interface defect density; and iii) the phase ratio should be easily manipulated for the purpose of tuning the dielectric and related EMW attenuation performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation